SAE Technical Paper Series 2002
DOI: 10.4271/2002-01-0222
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Comfort Analysis of an Automobile Driver with Heated and Ventilated Seat

Abstract: A thermal/physical model of the dynamic interaction between an automobile passenger, the cabin environment, and a heated/ventilated seat is presented. The model considers the human body as being made of 21 distinct segments and three-layers. Simple mathematical models are presented to simulate heating and ventilation of cool air through the seat.The model has the ability to predict the transient response of a driver in a highly non-uniform thermal environment in terms of local and overall thermal comfort level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…Good agreement between the theoretical and experimental results was reported. A thermal model of the dynamic interaction between an automobile passenger, the cabin environment, and a heated/ventilated seat was recently developed by Karimi et al (2002). The model considers the human body as being made of 21 distinct segments and three-layers.…”
Section: Introductionmentioning
confidence: 99%
“…Good agreement between the theoretical and experimental results was reported. A thermal model of the dynamic interaction between an automobile passenger, the cabin environment, and a heated/ventilated seat was recently developed by Karimi et al (2002). The model considers the human body as being made of 21 distinct segments and three-layers.…”
Section: Introductionmentioning
confidence: 99%
“…The contacting body (skin and clothing) was divided into control volumes extending from the seat surface toward the body core. The core temperature was considered to be fixed at 37°C during the simulations, which is consistent with the numerical results from a previous study (Karimi et al 2002). The room's average temperature was taken as ambient and wall surface temperature.…”
Section: Solution Methodsmentioning
confidence: 96%
“…Burch et al (1992aBurch et al ( , 1992b developed a mathematical model of thermal interactions between a driver and the interior environment of an automobile for which good agreement was reported between model predictions and jury data. This model was later extended by Karimi et al (2002 to predict the transient response of a driver in a highly nonuniform thermal environment. Constant thermal resistances were considered in the seat backrest and cushion areas to predict time variations of the seat and occupant temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The next issue was the modeling human physiology in I-DEAS. Detailed physiological models were available [4,5,8] by taking into account heat generation from the body and heat loss by perspiration, radiation, convection, etc.. Karimi et al [7] had shown that, using a variation of the Burch model [2] -the core temperature core temperature remained almost constant under severe weather conditions. Given that clinical hypothermia occurs when the core temperature goes below 2 AE C from normal, the occupant physiological model could be further simplified, by using a constant temperature source at (37 AE C) to represent the body core, as documented in Karimi et al [6].…”
Section: Combined Thermal-mechanical Simulationmentioning
confidence: 99%